Community Participation And Village Head Leadership In Village Fund Management In Baru Sungai Sakai Village, Tiang Pumpung District, Merangin Regency, Jambi Province - Reiny Erica Sonia; Sri Rahayu; Rico Wijaya Z (Citakonsultindo, 2026)
This study aims to analyze the influence of community participation and village head leadership on village fund management in Baru Sungai Sakai Village, Tiang Pumpung District, Merangin Regency, Jambi Province. The study used a descriptive quantitative approach with a survey method using a questionnaire. The study sample consisted of 132 heads of families selected using a purposive sampling technique. Data were collected through a structured questionnaire with a Likert scale of 1–5 that measured three main variables: community participation, village head leadership, and village fund management. The results showed that community participation was still relatively low, especially in the decision-making and program evaluation stages. The village head's leadership was also not yet effective, as reflected in low transparency, weak communication, and limited participation opportunities opened by the village head. These two factors together contributed to the suboptimal management of village funds in accordance with the mandate of applicable regulations.